Physical Activity Modifies the Association between C-Reactive Protein -Triglyceride - Glucose Index (CTI) and Dyslipidemia: Evidence from a 10-Year Chinese Cohort. - Wang, Yang; Luo, Zixuan; Zhou, Zihan; Zhang, Xiaoquan (Journal of Sports Science & Medicine, 2026)
Dyslipidemia is a major contributor to cardiovascular disease. The C-reactive protein - triglyceride - glucose index (CTI), which reflects insulin resistance and systemic inflammation, has increasingly been recognized as a potential marker for metabolic disturbances. However, its predictive value for incident dyslipidemia remains uncertain, and the role of physical activity in this association requires further clarification. This study pro-spectively examined the association between CTI and the risk of dyslipidemia, and further assessed whether physical activity modifies this relationship in middle-aged and older Chinese adults. A total of 7,954 participants aged ≥45 years without dyslipidemia at baseline were enrolled, using data from the China Health and Retirement Longitudinal Study (2011 - 2020). Physical activity was assessed using the CHARLS physical activity questionnaire, which captures the frequency and duration of vigorous, moderate, and light activities. Based on the frequency and duration of these activities, participants were categorized into low, moderate, and high physical activity groups. CTI was derived from high-sensitivity C-reactive protein, fasting plasma glucose, and triglyceride levels. Incident dyslipidemia was defined based on abnormal lipid profiles, ongoing lipid-lowering treatment, or a physician's clinical diagnosis. Cox proportional hazards regression with restricted cubic splines was applied to evaluate associations, with stratified analyses by sex, age, and physical activity level. During 10 years of follow-up, 2,011 new cases of dyslipidemia were recorded. Each 1-unit increase in CTI corresponded to approximately a 9% higher risk of dyslipidemia (HR = 1.09, 95% CI: 1.01 - 1.18). Individuals in the highest CTI quartile had a 15% greater risk compared with those in the lowest quartile (HR = 1.15, 95% CI: 1.01 - 1.30). Stronger associations were observed in men (HR = 1.20, 95% CI: 1.05 - 1.36) and adults aged 45 - 59 years (HR = 1.22, 95% CI: 1.08 - 1.39), whereas no significant effect was found in women. When stratified by physical activity, a 1-unit CTI increase was linked to about a 10% higher risk in the light and moderate activity groups, and to a 28% higher risk in the vigorous activity group, with risk plateauing at higher CTI levels. Elevated CTI was prospectively associated with an increased risk of dyslipidemia, particularly in men and individuals in midlife. Physical activity appeared to influence this relationship, suggesting that CTI could serve as a practical marker for early risk stratification. These findings underscore the importance of regular exercise in preventing dyslipidemia.